2014
DOI: 10.1007/s13762-014-0626-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heavy metal and total petroleum hydrocarbon contamination of roadside surface soil

Abstract: The present study was conducted along three major highways namely State Highway (SH49), National Highway (NH66 and 45A) connecting Puducherry (India) for assessing heavy metals and total petroleum hydrocarbon contamination from surface soils in close proximity at a depth of 0-15 cm into automobile repair workshops and agricultural fields located beside the highways. Contamination levels of copper, lead, zinc, manganese, cadmium and chromium were assessed in the surface sediments soil on the basis of geoaccumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Road transportation has increased alongside rapid economic development, resulting in a sprawling road network in China. Road transportation is one of the most significant sources of heavy metal pollution and plays an important part in the biogeochemical cycles of trace metals (Liu et al, 2009;Khan and Kathi, 2014). The combustion of liquid fuels, vehicular abrasion and the weathering of track or road materials can release particles containing heavy metals (Suzuki et al, 2009; Science of the Total Environment 521-522 (2015) [160][161][162][163][164][165][166][167][168][169][170][171][172] 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Road transportation has increased alongside rapid economic development, resulting in a sprawling road network in China. Road transportation is one of the most significant sources of heavy metal pollution and plays an important part in the biogeochemical cycles of trace metals (Liu et al, 2009;Khan and Kathi, 2014). The combustion of liquid fuels, vehicular abrasion and the weathering of track or road materials can release particles containing heavy metals (Suzuki et al, 2009; Science of the Total Environment 521-522 (2015) [160][161][162][163][164][165][166][167][168][169][170][171][172] 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the non-point source of heavy metal contamination is from vehicular traffic while the unregulated incineration and dumping sites of hazardous waste material along the highway were also responsible for point source contaminations. Further research by Khan and Kathi (2014) on heavy metal and petroleum hydrocarbon contamination of roadside surface soil from a site in close proximity to automobile repair workshop and agricultural field revealed that sampling sites in the proximity to automobile workshops were considerably polluted as compared to soil from agricultural fields along highways. This suggests a direct influence of anthropogenic activities on levels of contamination.…”
Section: *Corresponding Authormentioning
confidence: 98%
“…Otoyol kenarı topraklarında zaman içerisinde yoğun trafik akışı, meteorolojik koşullardan kaynaklı yol malzemesinin (asfalt/beton) aşınması, araç çeşitleri gibi faktörlerle ağır metal kirliliği gerçekleşmektedir (Şekil 5). [46], Çin [47], [48], Kore [49], Torino [50], Türkiye-Tekirdağ [51], Türkiye-Sakarya [52], Türkiye-Mardin [53], İran [54], Nijerya [55], Bangalore [56], Nijerya [57], Türkiye-Tekirdağ [58], Çin [59], İran [60], Abeokuta [61], Bangladeş [62], Hindistan [63], Suudi Arabistan [64], Kanada [65], Bangladeş [66], Nijerya [67], Hindistan [68] şeklinde literatürde yerini almıştır. Literatürde bazı çalışmalarda ise yol kenarında bulunan topraklarda trafikten kaynaklı ağır metal konsantrasyonları yol kenarındaki flora ve fauna üzerindeki seviyelerine ve etkilerine göre değerlendirilmiştir [69]- [73].…”
Section: Ağır Metallerin çEvreye Ve Insan Sağlığına Etkileriunclassified